Effects of palm oil fuel ash (POFA) towards consistency and setting time properties of concrete - Imran N.F.; Hasri M.N.; Fitri N.A.K.; Hasan D.; Ramli M.Z. (American Institute of Physics Inc., 2023)
Malaysia is having an environmental problem in disposing palm oil fuel ash (POFA) which is a byproduct of palm oil mill since many years ago. Due to this concern, it may be utilized in a concrete as one of the supplementary cementatious material (SCM). This research is to study its setting time of each sample by replacement of cement using liquidation and powder technique. The replacement percentage used for this research is 5% POFA and 10% POFA. Through this research, mixture with 5% POFA using liquidation technique has the highest setting time. 2018 Author(s).